Downregulation of ROR2 attenuates LPS‐induced A549 cell injury through JNK and ERK signaling pathways - Zhonglin Wang; Liu Yang (Immunity, Inflammation and Disease)
Abstract Background We aimed to determine whether receptor tyrosine kinase‐like orphan receptor 2 (ROR2) is involved in the occurrence of acute lung injury (ALI) by an animal study and explore the effect of ROR2 downregulation on lipopolysaccharide (LPS)‐treated human lung carcinoma A549 cells by a cytological study. Methods Murine models of ALI were successfully constructed by intratracheal instillation of LPS. Meanwhile, A549 cell line stimulated with LPS was used for a cytological study. The expression of ROR2 and its effect on proliferation, cell cycle, apoptosis, and inflammation were detected. Results It was found that LPS administration markedly inhibited the cell proliferation, resulted in cell cycle arrest at G1 phage, elevated levels of pro‐inflammatory cytokines and apoptosis rate of A549 cells. However, LPS‐mediated adverse effects mentioned above were significantly ameliorated by downregulation of ROR2 in comparison with LPS treatment. In addition, administration of ROR2 siRNA notably decreased the phosphorylation level of c‐Jun N‐terminal kinase (JNK) and extracellular signal‐regulated kinase (ERK) in LPS‐challenged A549 cells. Conclusions Thus, the present data indicate that downregulation of ROR2 may decrease LPS‐induced inflammatory responses and cell apoptosis through inhibiting JNK and ERK signaling pathway, which attenuates ALI.